Pengaruh Foot Care Education Melalui Media Audiovisual Terhadap Tingkat Pengetahuan Pasien Diabetes Mellitus - Natalia Nadia Azalia Dyah Wibowo; Muhammad Anis Taslim; Felicia Risca Ryandini (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Diabetes Mellitus, DM, refers to chronic metabolic problems indicated by hyperglycemia condition. This matter influences complications on the feet. Foot care education is a diabetic education to treat the feet excellently and correctly by providing audiovisual media. This research analyzed the influence of foot care education taught by audiovisual media toward the improvement of DM knowledge of DM patients. This quasi-experimental research used a control group design. The sampling technique was incidental sampling with 60 respondents. The Wilcoxon test result obtained a p-value of 0.0001 lower than 0.05. The result indicated the influence of foot care education with audiovisual media on the DM knowledge improvement of the patients. The researchers expect future researchers to apply foot care education with audiovisual media to prevent diabetic foot cases.